Efficacy of spray administration of formalin-killed Streptococcus agalactiae in hybrid red tilapia - Omar, Noraini; Mohd Yusoff, Sabri; Abdullah, Siti Zahrah (Taylor & Francis, 2013)
An initial evaluation of spray vaccination was carried out with 60 hybrid Red Tilapia Oreochromis spp., divided into three groups that consisted of 10 fish per group with duplicates. The formalin-killed cells (FKCs) of Streptococcus agalactiae were administered once to group 1 by spray and once daily for five consecutive days to group 2. Group 3 remained as the untreated control group and was sprayed with normal saline. A booster was given twice to all the groups, once at the second week and again at the fourth week after the first vaccination. After this initial evaluation, a challenge study was conducted with 40 tilapia divided into two groups that consisted of 10 fish per group with duplicates. Group 1 was vaccinated with FKCs of S. agalactiae by a single spray administration while group 2 remained as the untreated control group. A booster was given twice using the same protocol as in the initial evaluation. After 6 weeks, fish from one of the duplicate tanks from each of groups 1 and 2 were challenged with pathogenic S. agalactiae by intraperitoneal (IP) injection, while fish in another tank were challenged through immersion. Based on the observations, serum immunoglobulin M (IgM) levels were significantly higher (P < 0.05) in the challenged fish than in the either the preexposed fish or the control group 1 week after the initial exposure. However, no significant differences (P > 0.05) were noted between challenged groups 1 and 2. In addition, no significant differences (P > 0.05) were observed between the frequencies of exposure. The mucus IgM level, however, remained high after each booster until the end of the 8-week study period. Meanwhile, serum IgM levels decreased after the challenge. A higher percentage of survival was noted for fish challenged through immersion (80%) compared with IP injection (70%). These results suggested that single spray exposure was able to induce IgM, which gave moderate to high protection during the challenge study.